NFV Service Chain Resource Allocation Technology - Hong Tang; Yujia Luo (Dianxin kexue)
SDN/NFV provides supporting technologies on network re-architecture and evolution for network operator.Service chain and related networking technology is becoming a significant use case of NFV,of which resource allocation is one of the key research points.The service chain status in quo was studied.The resource allocation mechanisms and related problems were analyzed.After that,a service function chain resource allocation scheme,which optimizes the usage of the network resource and realizes virtual network function instance deployment and route selection,was proposed.Experiment results show that the proposed method is able to serve more traffic.